The Resistance Mechanism Governs Physiological Adaptation of Escherichia coli to Growth With Sublethal Concentrations of Carbapenem - Schäfer, Franca; Görner, Pia; Woltemate, Sabrina; Brandenberger, Christina; Geffers, Robert; Ziesing, Stefan; Schlüter, Dirk; Vital, Marius (Frontiers in Microbiology, 2022)
Factors governing resistance in carbapenem-resistant Enterobacteriaceae are manifold. However, despite ample research efforts, underlying molecular mechanisms are still only partly understood. Furthermore, little is known on (eco)physiological consequences from resistance acquisition originating from distinct mechanisms in respective bacteria. In this study, we examined physiological adaptation of Escherichia coli clinical isolates exhibiting two distinct resistance mechanisms – either carrying a carbapenemase (n=4; CARB) or alterations of porin-encoding genes (n=6; POR) – during growth with sublethal concentrations of ertapenem in chemostat culture. Basic growth parameters based on optical density and flow-cytometric analyses as well as global gene expression patterns using RNA-Seq were recorded. We demonstrate that strategies to deal with the antibiotic were distinct between strains of the two groups, where (increased) expression of carbapenemases was the only response in CARB, whereas wide-spread alterations in gene-expression that promoted a survival-like phenotype was observed in POR. The response in POR was accompanied with “costs of resistance” resulting in reduced growth efficiencies that are intrinsic to that group and were also observed during growth without antibiotic challenge, however, at lower levels. All strains showed similar minimal inhibitory concentrations and did not form phylogenetic groups, indicating that results cannot be attributed to distinct resistance levels or phylogenetic relationships, but are indeed based on the resistance mechanism.